Report of the Working Group on Empowering the Scheduled Tribes for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
Planning Commission has constituted a Working Group on the Empowerment of Scheduled Tribes during Tenth Five Year Plan to review the existing approach, strategies, priorities etc. and to suggest rationalization, minimization of the on going programmes and effective intrasectoral convergence. One of the items of terms of reference is to review the manner of utilization of special central assistance to TSP and grant-in-aid under Article 275(1) of the Constitution and to suggest necessary measures to improve their effectiveness.
Government of India, Planning Commission